Inside Women’s Robes: Masculinity and Dress During Èró Festival - Abiona, Ayodeji (Matrix)

(untitled) (International Network for Training, Education, and Research on Culture, 2025)
In literature, the Yorùbá feature prominently in discussions on rituals, festivals, and gender in socio-cultural practices. The Yorùbá, like many other African societies, is patriarchal. However, in practice and literature, reference to femininity and female agency is rife. Èró festival is a community-wide feast where men don feminine attires and process around the community. This article considers cross-dressing during traditional festivities as a symbol of feminine power, a gesture to female inclusivity, and a tool of social cohesion in a Yorùbá community. In order to interrogate the centrality of Èró festival – a matricultural complex – to the continued existence of the community, the paper relies on the abundant literature on Yorùbá religion, culture, and particularly, gender relations. It combines an analysis of these with oral interviews with recent participants in the festival and other traditional observances to analyze dress as a gendered item in festive cultural practices among the Yorùbá. The paper presents evidence of gender and dress both in literature and practice, limiting itself to Ùṣò in eastern Yorùbáland. It argues that female power, informed by their biologically-derived endowment, is ubiquitous and potent among the Yorùbá. In Ùṣò, men enact this feminine power through the symbology of dress.